Bringing back our deserts - MacCarald, Clara, 1979- (Conservation success stories., 2018)
Examines the damage inflicted on the planet's deserts, their environmental importance, and the efforts being made to protect and restore them. Includes diagrams, a glossary, resources for further information, and color photographs.